Nego-feminism as a bridge between patriarchy and matriarchy in Zaynab Alkali's The Stillborn and The Virtuous Woman - Muhammad, Usman Ambu; Mani, Manimangai; Talif, Rosli; Jujar Singh, Hardev Kaur (Universiti Putra Malaysia Press, 2017)
The Stillborn (1984) is Zaynab Alkali’s debut novel that captured the attention of many researchers and critics alike. The Virtuous Woman (1986) that arrived two years after has not attracted much critical attention. Alkali is a prominent Nigerian female writer, whose concern is always the place of a girl-child in a patriarchal African society. Literary reviews on the texts have highlighted concept of women oppression and their emancipation (Okereke, 1996, Razinatu and Kurfi, 2011). Alkali believes that, it is only education that can play the role of emancipation of a girl-child in a patriarchal society. In The Stillborn and The Virtuous Woman, Alkali attempts to prove this by portraying a female character (Li) in The Stillborn who triumphs at the end both educationally and economically. And in The Virtuous Woman three female characters are portrayed as successful ones educationally. But in so doing, Alkali seems to alienate the male characters in the two texts. The objective of this paper is to examine the aspect that is given less attention hitherto – the female dominance over the male character(s) as portrayed by the author. It also uses textual analysis as the methodology in analyzing the two texts. Nego-feminism is the theory to be used as conceptualised and theorised by Obioma Nnaemeka (1999). It is a new feminist theory which is hoped to be used as a negotiating tool between patriarchy and matriarchy. The expected finding hopes to create a better and balanced society that accommodates the sexes.